1988
DOI: 10.1016/0014-5793(88)80696-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence digital image analysis of the inositol trisphosphate‐mediated calcium transient in single permeabilized parietal cells

Abstract: The myo-inositol 1,4,5trisphosphate (IPs)-induced Caz + mobilization in single saponin-permeabilixed and fura-2-loaded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Our results are consistent with the existence of at least two distinct Ca2+ stores in parietal cells, since caffeine can further release Ca2+ in permeabilized cells even after depletion of Ca2+ stores provoked by a maximal concentration of Ins(1,4,5)P3. These results are in agreement with a previous report [41], which showed that Ins(1,4,5)P3 can partially release Ca2+ from intracellular Ca2+ stores in permeabilized parietal cells. Moreover, Tsunoda et al [43] demonstrated that in parietal cells gastrin can induce Ca2+ waves propagating within the cytosol, consistent with the existence of two different Ca2+ stores in this cell type.…”
Section: Gastrin Receptor and Muscarinic Receptor Regulate Common Ca2supporting
confidence: 94%
“…Our results are consistent with the existence of at least two distinct Ca2+ stores in parietal cells, since caffeine can further release Ca2+ in permeabilized cells even after depletion of Ca2+ stores provoked by a maximal concentration of Ins(1,4,5)P3. These results are in agreement with a previous report [41], which showed that Ins(1,4,5)P3 can partially release Ca2+ from intracellular Ca2+ stores in permeabilized parietal cells. Moreover, Tsunoda et al [43] demonstrated that in parietal cells gastrin can induce Ca2+ waves propagating within the cytosol, consistent with the existence of two different Ca2+ stores in this cell type.…”
Section: Gastrin Receptor and Muscarinic Receptor Regulate Common Ca2supporting
confidence: 94%
“…It seems likely that this rapid increase in Ins(I,4,S)Pj content may bc related to the already described [r-lo] peak increase in intracellular (Ca'* ] induced by gascrin: (i) the time course of Ins (l,4,5)P~ accumulation fits in well with that of intracellular (Ca2+ ] increase, (ii) both events are independent on extracellular Ca2 * [9] and (iii) Ins(l,4,5)P3 was shown to induce a rapid rise in intracellular [Ca'"] in pcrmeabilized gastric parietal cells [33,34].…”
Section: I~~(l45)~3mentioning
confidence: 98%
“…The curve can be established in vitro (i.e. using solutions of the stain in a series of buffers at different pH) or in vivo (using labeled For calcium the in vitro calibration approach proposed by Grynkiewiez et al [195] is generally adopted [197][198]:…”
Section: ) Pellet Convex Area -Core Convex Areamentioning
confidence: 99%